2013
DOI: 10.3844/ajptsp.2013.95.101
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORATION OF HEALING PROMOTING POTENTIALS OF LEAVES OF <i>MORUS ALBA</i> L. IN ALBINO RATS

Abstract: To establish the wound healing activity of aqueous and ethanolic extract of roots of Morus alba. Two models were performed to evaluate the wound healing activity i.e., Incision and Excision model. In incision model the parameter which was carried out was breaking strength of wounded skin. In excision model percentage wound contraction and period of epithelialization was established for both the extracts. Reference standard drug was Aloe vera ointment for comparison with other groups. From the observation in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Wound healing is stepwise process, which consists of different phases such as hemostasis, inflammation, proliferative and remodeling (Kaushik et al, 2013). This process is often negatively affected by microbial infection or pathological condition leading into a development of chronic wound (Polakovicova et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing is stepwise process, which consists of different phases such as hemostasis, inflammation, proliferative and remodeling (Kaushik et al, 2013). This process is often negatively affected by microbial infection or pathological condition leading into a development of chronic wound (Polakovicova et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Golongan senyawa bioaktif yang terkandung dalam tanaman murbei (Morus alba L.) sebagian besar merupakan zat polifenol, flavonoid, antosianin, lektin, oligosakarida, glikosida, zat anti-bakteri, asam lemak tak jenuh yang terdapat pada daun, batang, buah dan akar (Lin & Lay, 2013). Golongan kandungan kimia yang lain telah dilaporkan seperti tanin, steroid, saponin dan senyawa kimia lainnya (Kaushik et al, 2013). Bagian batang murbei mengandung senyawa seperti triterpenoid (alfa-betaamyrin, sitosterol, sitosterol-alfa-glucoside), kumarin (umbelliferone dan scopoletin) dan flavonoid (morusin, siklomorusin dan oxyhidromorusin).…”
Section: Pendahuluanunclassified
“…For these reasons, the total demand of the world market for herbal products is at around $83 billion, and Europe accounts for over 50% of the total. A previous study suggested the potential healing action by performing test on treatment with MA extract (Kaushik et al ., ). However, it was not sufficient to explain the mode of action of the extract nor wound epithelialization at the molecular level.…”
Section: Introductionmentioning
confidence: 97%